PENGARUH LITERASI TEKNOLOGI TERHADAP KUALITAS PEMBELAJARAN GURU SEKOLAH DASAR DI KABUPATEN MAGELANG - Ajeng Ngesty Pujawati; Galih Istiningsih; Irham Nugroho (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The transformation of education in the era of the Industrial Revolution 4.0 and Society 5.0 has brought fundamental changes to the role of elementary school teachers. Teachers are expected to possess technological skills as well as expertise in managing the learning process so that synergy between technological literacy and pedagogy can be created, which in turn enhances the effectiveness and quality of learning in a sustainable manner. This quantitative study analyzes the relationship between teachers’ technological literacy and the quality of learning. Data were collected through questionnaires distributed to 21 teachers across 9 sub-districts in Magelang Regency. The level of teachers’ technological literacy and learning quality was measured using a Likert scale. Bivariate and multivariate analyses, including correlation and regression modeling, were conducted to explore the influence of teachers’ technological literacy on learning quality. The findings indicate that teachers’ technological literacy contributes 70.6% to the quality of learning, while the remaining 29.4% is influenced by other factors.